2016
DOI: 10.4081/idr.2016.6275
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Administrative and Clinical Data for Central Line Associated Blood Stream Infections in Pediatric Intensive Care Unit and Pediatric Cardiothoracic Intensive Care Unit

Abstract: Central line associated bloodstream infections (CLABSIs) are a frequent source of health complication for patients of all ages, including for patients in the pediatric intensive care unit (PICU) and Pediatric Cardiothoracic Intensive Care Unit (PCTU). Many hospitals, including the University of Michigan Health System, currently use the International Classification of Disease (ICD) coding system when coding for CLABSI.The purpose of this study was to determine the accuracy of coding for CLABSI infections with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The sensitivity of ICD-coding (9th or 10th edition) is generally low, in five of the seven studies that use this as the sole variable of the algorithm [11,39,54,70,77,78,83]. The two studies with sensitivities of 0.86 and 0.97 focused on SSI after coronary artery bypass graft surgery and total joint replacement [39,54].…”
Section: International Classification Of Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity of ICD-coding (9th or 10th edition) is generally low, in five of the seven studies that use this as the sole variable of the algorithm [11,39,54,70,77,78,83]. The two studies with sensitivities of 0.86 and 0.97 focused on SSI after coronary artery bypass graft surgery and total joint replacement [39,54].…”
Section: International Classification Of Diseasesmentioning
confidence: 99%
“…Another approach to automated surveillance of BSI is the reuse of the ICD-coding system. Unfortunately the performance to detect BSI in the paediatric ICU was shown to be very poor (sensitivity of 0.32), as Bond et al showed [78]. In contrast, one adult ICU-tailored algorithm showed excellent performance characteristics (sensitivity and specificity of 1) [28].…”
Section: Bloodstream Infections (Including Central Line Associated)mentioning
confidence: 99%
See 1 more Smart Citation
“…Automated surveillance algorithms for CVC-BSI have been developed [ 13 26 ]. However, to our knowledge, the majority were based on an ICU population [ 13 19 ], were semi-automated [ 13 16 , 20 23 ], and nearly all used the central line-associated BSI (CLABSI) criteria of the Centers for Disease Control and Prevention (CDC) as reference [ 13 15 , 17 26 ] and none the microbiologically confirmed CVC-BSI (CRI3-CVC) definition of the European Centre for Disease Prevention and Control (ECDC).…”
Section: Introductionmentioning
confidence: 99%